2015
DOI: 10.17953/1545-0317.13.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Rewards in Wealth Building: Asian American Homeownership and Foreclosure Pre and Post Housing Boom in East San Gabriel Valley, California

Abstract: While much research exists on African Americans and Latinos after the housing crisis in 2007, much less is known about the Asian American experience particularly as it relates to foreclosure and housing burden. This study takes a quantitative case study approach examining Asian Americans in one region of Los Angeles County. Utilizing data from the Census, Home Mortgage Foreclosure Data, and Data-Quick, we provide a more comprehensive picture of the Asian American housing experience before, during and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Patraporn et al. () examined affluent and racially diverse neighborhoods of East San Gabriel Valley, California, and found that Asian Americans had lower default and foreclosure rates than other groups in part because Asian homeowners were less likely to have subprime and/or variable interest loans. Additionally, homeowners in Los Angeles's middle‐class Asian and Latino neighborhoods had similar or lower foreclosure rates than homeowners in White areas (Lee ).…”
Section: What We Know About How Place Affects Foreclosure Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…Patraporn et al. () examined affluent and racially diverse neighborhoods of East San Gabriel Valley, California, and found that Asian Americans had lower default and foreclosure rates than other groups in part because Asian homeowners were less likely to have subprime and/or variable interest loans. Additionally, homeowners in Los Angeles's middle‐class Asian and Latino neighborhoods had similar or lower foreclosure rates than homeowners in White areas (Lee ).…”
Section: What We Know About How Place Affects Foreclosure Riskmentioning
confidence: 99%
“…For example, foreclosed properties in Southern California Latino neighborhoods with more Black residents and lower-income residents took longer to sell than properties in Latino neighborhoods with fewer Blacks and higherincome residents (Pfeiffer and Molina 2013). Patraporn et al (2015) examined affluent and racially diverse neighborhoods of East San Gabriel Valley, California, and found that Asian Americans had lower default and foreclosure rates than other groups in part because Asian homeowners were less likely to have subprime and/or variable interest loans. Additionally, homeowners in Los Angeles's middle-class Asian and Latino neighborhoods had similar or lower foreclosure rates than homeowners in White areas (Lee 2018).…”
Section: How Neighborhood Racial Demographics Link To Foreclosure Riskmentioning
confidence: 99%
See 2 more Smart Citations